Screening for depression among community-dwelling elders: Usefulness of the center for epidemiologic studies depression scale - Sebind Kumar; Anisha Nakulan; Sumesh Purushothaman Thoppil; Rejani Parameshwaran Parassery; Shaji Sivaraman Kunnukattil (Indian Journal of Psychological Medicine, 2016)
Context: Though common, depressive disorders often remain undetected in late life. Aim: To examine the usefulness of Center for Epidemiologic Studies Depression (CES-D) for identifying depression among older people. Settings and Design: Community resident older people (aged 65 years or more), were evaluated by clinicians trained in psychiatry, as part of a cross-sectional study of late-life depression. Assessments were done in the community. Methods and Material: The participants were assigned ICD-10 diagnoses and assessed using Montgomery-Asberg Depression Rating Scale (MADRS) and CES-D. A short version of CES-D with 10 items, translated to the local language Malayalam, was used. Statistical Analysis: The sensitivity and specificity of CES-D was evaluated against ICD-10 clinical diagnosis of depression. The correlation of CES-D and MADRS was assessed using Pearson correlation coefficient. Results: 220 consenting adults from 3 wards of the Panchayath were assessed. On analysis of the Receiver Operating Characteristic (ROC) curve of CES-D scores in relation to clinical diagnosis, the large Area Under Curve (AUC) showed efficient screening and a cut off score of 4 in CES-D had a sensitivity of 97.7% and a specificity of 79.1% for depression. There was also good correlation between the MADRS and CES-D scores (0.838). Conclusion: CES-D is a short simple scale which can be used by health care professionals for detecting depression in older people in primary care settings.